Rheology of whey protein solutions and gels : thesis submitted for the degree of Doctor of Philosophy in Food Technology at Massey University, New Zealand - Tang, Qingnong (Massey University, 1993)
The use of whey protein products in foods is governed by their nutritional and functional properties. Whey protein products have increasingly been applied in a variety of food systems as functional ingredients. In order to boost applications of whey protein products and to improve, predict and control their functional attributes in food products knowledge is required about how they behave functionally under different conditions, e.g. when product composition, processing history, protein concentration, pH, salt concentration and temperature vary. The flow properties of whey protein concentrate solutions were studied in a Bohlin rheometer. The effects of protein concentration, temperature, pH and salts on the gelation and gel properties of whey protein concentrates and whey protein isolate were also investigated in the same rheometer. Differences in gelation between whey protein concentrates, whey protein isolate, egg white and B-lactoglobulin were studied. Differences between dynamic shear properties determined in a Bohlin rheometer and fracture properties determined in an Instron universal testing machine were also studied. The flow properties of whey protein concentrate solutions changed from Newtonian to pseudoplastic or even thixotropic behaviour, owing to structure formation in the solutions, i.e. to increases in protein intermolecular interactions. Such structure formation resulted from increases in protein concentration, temperature or CaC12 concentration, and from shifting the pH to extreme values. Gelation of whey protein was dependent on protein concentration, gelation temperature, pH, salt content and lactose content. Salt content was the most important factor in determining the gelling properties of various whey protein concentrate products and whey protein isolate. Consistent gelling properties could only be achieved when salt content was carefully controlled. The degree of protein denaturation and lactose content also led to differences in gelling behaviour of whey protein concentrates. Whey protein products, when compared with ·egg white, had a higher gelation temperature, a higher minimum protein concentration for gelation, lower initial gelation rate and lower gel stiffness. The differences in initial gelation rate and gel stiffness could be compensated by adjustment of the salt content of whey protein products. Dynamic viscoelastic measurements on whey protein isolate gels in the region of the sol-gel transition exhibited simple power law relationships between the storage (G' ) and loss (G") moduli and frequency as G' oc ro0·54±0.o2 and G" oc ro051±0.o2 , indicating that the gel in the region of the sol-gel transition could have the geometry of a fractal. The critical exponents calculated from the protein concentration dependence of gelation time and from the site percolation model indicated that the gelation of whey protein is a realization of a percolation process. Compression rigidity modulus (Ec), penetration rigidity (EP), tension rigidity (EJ and storage modulus G' all exhibited a similar pattern of variation with pH. G' , Ec, EP and Ev which were not closely related to the fracture properties and hardness of whey protein concentrate gels, were controlled by electrostatic interactions. The fracture forces and hardness were determined by both disulphide bonds and electrostatic interactions, while fracture strains were mainly controlled by disulphide bonds.
Keywords: Whey proteins; Whey protein products